The global lung function initiative 2021 (GLI-2021) norms provide mixed results for static lung volumes (SLVs) in Algerian adults. Issue 1 (31st December 2022) - Ketfi, Abdelbassat; Ben Saad, Helmi
ABSTRACT: The validity of the GLI-2021 norms for SLVs in healthy Algerian adults has not been assessed. To ascertain how well do the GLI-2021 norms fit to contemporary SLVs data in Algerian adults. This was a cross-sectional study involving 481 (n = 242 females) healthy non-smoking adults recruited from the Algiers general population. All participants underwent a clinical examination and a plethysmography. Z-scores for slow vital capacity (SVC), functional residual capacity (FRC), residual volume (RV), total lung capacity (TLC), expiratory reserve volume (ERV), inspiratory capacity (IC), and RV/TLC were calculated. The mean difference between the determined and the predicted values (∆value) of SLVs were calculated. The GLI-2021 norms would be considered as reflective of contemporary Algerian SLVs if the total sample mean z-scores were in the normal range ( ie ; −0.5 to +0.5). The participants' means ± SDs of age and height were 46.4 ± 16.4 years and 166 ± 10 cm, respectively. The determined SLVs were significantly different from those predicted (∆values means ± SDs were −170 ± 470 ml for IC, −100 ± 490 ml for SVC, 170 ± 400 ml for ERV, 240 ± 620 ml for TLC, 370 ± 340 ml for RV, 480 ± 480 ml for FRC, and 5.28 ± 4.38% for RV/TLC). The means ± SDs z-scores for IC, SVC, ERV, and TLC were in the normal range (−0.29 ± 0.88, −0.17 ± 0.94, 0.29 ± 0.77, and 0.35 ± 0.86, respectively), but those of RV, FRC, and RV/TLC were out of the normal range (0.74 ± 0.66, 0.75 ± 0.72, and 0.83 ± 0.75, respectively). In healthy Algerian adults, the GLI-2021 norms fit well to SVC, TLC, ERV, and IC, but they do not fit to FRC, RV, and RV/TLC.